Pengaruh Media Flipbook Terhadap Pemahaman Konsep Pada Materi Wujud Zat Dan Perubahannya Di Kelas IV SD Negeri 1 Airgegas - Neilizah Pargita; Yuanita; Erika Fitri Wardani (Universitas Muhammadiyah Bangka Belitung, 2026)
This research addresses the observed difficulties students face in understanding the concept of phase changes in matter, as well as the limited use of digital media in instruction. Furthermore, Flipbook media has not previously been integrated into the learning process. The study aims to examine the effect of Flipbook media on grade IV students' conceptual understanding of states of matter and phase changes at SD Negeri 1 Airgegas. A quantitative approach was employed using a pre-experimental, one-group pretest-posttest design. The study was conducted at SD Negeri 1 Airgegas during the first semester of the 2025/2026 academic year, involving 21 grade IV students selected through saturated sampling. Data were collected through testing, and analysis was performed using paired-samples T-tests and the Shapiro-Wilk normality test. The results showed an average pretest score of 46.81 and a posttest score of 66.19. The normality test values for the pretest (0.131 > 0.05) and posttest (0.134 > 0.05) indicated that the data were normally distributed. The hypothesis test produced a p-value of 0.000, which is less than 0.005, leading to the acceptance of Ha and rejection of Ho. These findings indicate that Flipbook media positively influences grade IV students' understanding of the concepts of substance, form, and phase changes at SD Negeri 1 Airgegas.